Uji Aktivitas Antibakteri Ekstrak Daun Wundu Watu(Alpinia Monopleura) Terhadap Pertumbuhan Bakteri Streptococcus Mutans (Atcc 25175) Penyebab Karies Gigi - AFDILLA, NIA; Muh. Asman Setiawan; Prayoga Ridha Faizal (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2025)
Alpinia monopleura is a plant that belongs to the Alpinia genus family which is a large genus of the Zingiberaceae family, which is widespread in many tropical regions including Indonesia. Antimicrobial compounds owned by wundu watu leaves include volatile oils, lignin, saponins, flavonoids, diterpenoids, and phenylpropanoids. The purpose of this study was to determine the inhibition of wundu watu leaves (Alpinia monopleura) against the growth of Streptococcus mutans bacteria. The type of research used is laboratory experimental, namely 5 treatment groups where 3 groups of Wundu watu leaf extracts with concentrations of 20%, 40%, and 60%, and 2 control groups, namely positive control (Amoxillin), and negative control (sterile Aquades). The inhibition test was carried out using the well method against Streptococcus mutans bacteria for 24 hours and then incubated at 37ºC which then measured the inhibition (mm). Measurement of the inhibition test was carried out using a caliper. The results showed that wundu watu leaf extract (Alpinia monopleura) can inhibit the growth of Streptococcus mutans bacteria with a weak category with an average diameter of the inhibition zone for concentrations of 20% which is 00 mm, 40% which is 0.3 mm, 60% which is 1.38 mm, positive control Amoxilllin which is 22.54 mm and negative control sterile distilled water which is 0.0 mm. Based on the Kruskall Wallis test results obtained sig 0,011 (sig < 0.05), it can be concluded that there is a significant difference in the diameter of the inhibition zone at various concentrations.